Organophosphorus Compounds and Brain GABAergic System - Zohreh Zare; Moslem Mohammadi (Journal of Mazandaran University of Medical Sciences, 2017)
Organophosphorus (OP) compounds are cholinesterase inhibitors widely used as pesticides in agriculture and nerve agents in battlefields. Exposure to these compounds leads to accumulation of acetylcholine at cholinergic synapses and overstimulation of muscarinic and nicotinic receptors by inhibiting the enzyme acetylcholinesterase. Seizure activity is one of the major manifestations of OP poisoning that is produced as a result of hyperstimulation of brain muscarinic receptors and subsequent recruitment of other neurotransmitter systems. Disruption of the excitatory/inhibitory balance can lead to OP-induced seizure activity and subsequent brain damages. Gamma-aminobutyric acid (GABA), the main inhibitory neurotransmitter in mammalian central nervous system, is synthesized from glutamate by glutamic acid decarboxylase and modulates neuronal excitability. After release, GABA binds to two different types of receptors: ionotrpic (GABAA and GABAC) and metabotropic (GABAB) receptors. Drugs that enhance GABAA-mediated inhibition are effective in treatment of OP-induced seizures. There is discrepancy in the literatures regarding changes on brain GABAergic system during OP intoxication. This review discusses the mechanism and toxic effects of OP compounds, brain GABAergic system, and how it changes following exposure to OP compounds.